Consumer protection in cases of unfair commercial practices, misleading advertisements, and defective products - Gaikeviča, Dana (Riga Graduate School of Law, 2022)
Consumer protection has always been an important element in the laws of every country and for good reason, because consumers bring profit, and this improves the economic situation of the country. But the excessive desire to dominate the market led to bad business practices, along with misleading advertisements and defective products. To keep consumers safe and protected, new laws have been formed to protect consumers and their economic well-being. The creation of the directive of uniform legislation for the European Union influenced the fact that national legislation had to be close to uniform requirements, however, weaker consumer protection than in the directive is prohibited. In connection with the information mentioned above, this study is aimed at studying the main issue of the implementation of consumer protection in three areas: unfair commercial practices, misleading advertisements, defective products. The bachelor thesis is based on case law and comparative methods of analysis.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Consumer protection law; Unfair Commercial Practice Directive